Kinetically Controlled Lifetimes in Redox-Responsive Transient Supramolecular Hydrogels - Wojciechowski, Jonathan P; Martin, Adam D; Thordarson, Pall (Journal of the American Chemical Society, 2018)
It remains challenging to program soft materials to show dynamic, tunable time-dependent properties. In this work, we report a strategy to design transient supramolecular hydrogels based on kinetic control of competing reactions. Specifically, the pH-triggered self-assembly of a redox-active supramolecular gelator, N,N'-dibenzoyl-l-cystine (DBC) in the presence of a reducing agent, which acts to disassemble the system. The lifetimes of the transient hydrogels can be tuned simply by pH or reducing agent concentration. We find through kinetic analysis that gel formation hinders the ability of the reducing agent and enables longer transient hydrogel lifetimes than would be predicted. The transient hydrogels undergo clean cycles, with no kinetically trapped aggregates observed. As a result, multiple transient hydrogel cycles are demonstrated and can be predicted. This work contributes to our understanding of designing transient assemblies with tunable temporal control.